Vibration Characteristics and Reduction Analysis of the Lifting Pipe Below Sea Wave - Sabaruddin Rahman (Collaborate Engineering Daily Book Series, 2023)
The effect of vibration dampening on lifting pipes in deep sea mining has attracted more and more attention in the last three decades; however, there are very few reports in the literature on the influence of ocean currents on pipe vibrations. Considering the geometric features of the prototype, this paper establishes the physical, mathematical, and simulation models of the lifting subsystem. A comprehensive finite element model for a deep sea mining system by OrcaFlex was developed to explore the influence of prop mass and sailing speed on deflection angles and axial loads and stresses of lifting pipes. Analytical and numerical simulations have been formulated to describe the variation rules of longitudinal vibration and axial stress at pump and buffer positions for the lifting subsystem to determine dynamic vibration damping parameters. This paper uses MATLAB and Orcaflex software to verify the mathematical model. The simulation results show that the installed DVA can effectively reduce the axial stress and longitudinal displacement at specific positions of the lifting pipe.